Secondary cystic adenomyosis in a young woman: a case report - Hong-Xuan Li; Ke-Juan Song; Nan-Nan Xia; Xiao-Yu Ji; Lei Sui; Qin Yao (Clinical and Experimental Obstetrics & Gynecology)
Background: Cystic adenomyosis (CA) is a rare form of adenomyosis. Case: We present for the first time secondary CA in a young woman with increased menstrual volume as the main clinical manifestation. A 23-year-old woman with a history of two uterine surgeries was hospitalized with increased menstrual flow volume and no dysmenorrhea or other discomfort. Ultrasound resulted in misdiagnosis as myoma of the uterus. She underwent laparoscopic surgery for adenomyoma excision with levonorgestrel-releasing intrauterine system (LNG-IUS) placement. During surgery, the lesions were completely removed under ultrasound guidance, and a specimen bag was used to reduce residual lesions in the abdominal cavity. She was postoperative treated with gonadotropin-releasing hormone analog (GnRH-a). Surgical findings and postoperative pathology confirmed CA. She has been followed up for 2 years without recurrence. Conclusions: A CA diagnosis should be considered for clinical manifestations of increased menstrual volume and dysmenorrhea in young patients with previous uterine surgery histories. Magnetic resonance imaging (MRI) is very important for CA diagnosis. Conservative surgery along with GnRH-a and LNG-IUS therapy can effectively prevent recurrence.